A paternidade sob a ótica do afeto - Maciel, Telma Djanira (2017)
The present work aims at the study of paternity under the optics of the affection and their influence in the Brazilian Civil law. Despite the continuous and exhaustive debate on the subject in academia in the last ten years, spreading with the decisions of the Superior Court of Justice and the Supreme Federal Court, the study is justified to the extent that, although the combination of understandings signed both in doctrine, as the case law on its importance for the existence of bills in Congress that seek to delineate the contours of the Institute, and should receive highlight the Bill n° 6.583/2013, named the Family Status and the Senate Bill n° 470/2013, without forgetting the other pretensions of Congressmen in the regularisation of affection in the Statute of the Child and Adolescent. Other points to be briefly addressed are the affection principle and the phenomenon of parenting affection in view of the Courts and of the doctrine. Analyze the constitutional parameters, as well as the acts and legal facts that characterize the paternity affection and its effects, both patrimonial and personal. There is still a brief comparative study of the existence of the phenomenon in other legal systems of other countries. It is concluded that it is permissible to talk about fatherhood as an affection acclaimed both in doctrine, both in doctrine and in jurisprudence, as a precondition for the formation of family links currently assumed and respected (despite contrary voices) and its effects on family law